Ultra-high performance concrete made from the insertion of glass residues as supplementary cement material (Research, Society and Development, 2021)
Portland cement concrete manufacturing techniques in the world have an immense variability, since each location concentrates natural resources with unique characteristics, sometimes similar, but with always different process conditions, such as: labor, equipment, environmental conditions, processing, storage, among others. The aim of this work is to develop cementitious composites partially replacing mineral admixtures by powdered glass residues, evaluating the physical-mechanical behavior through axial compression strength, as well as the production of hydrated phases through x-ray diffraction, both at 28 days. Cement, silica fume, metakaolin, powder glass residue, polycarboxylic ether-based superplasticizer, and low temperature water were used to prepare different compositions of ultra-high performance concrete. The preparation took place with the aid of a mechanical bench mixer, and the densification was carried out with the aid of an immersion vibrator in cylindrical molds 50 x 100 mm. After unshaped, the specimens received heat treatment, with isotherm at 60°C for 36 hours, followed by wet curing in a tank saturated with calcium hydroxide, until the tests of compression strength and x-ray diffraction were carried out. The results show that the composition added with the residue, replacing metakaolin, behaved in an adequate manner, with compressive strength equivalent to the reference composition (silica fume + metakaolin), as well as the production of the same hydrated compounds. However, the application of only the glass residue or metakaolin reduced the intensity of the pozzolanic reactions, justified by the presence of a high content of calcium hydroxide in the compositions, which allows us to conclude that the powder glass residue presents viability as a filler, when replacing metakaolin in the presence of silica fume, as it does not compromise the performance of the mixtures made.